(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The right to life and personal liberty is the most fundamental of all the fundamental human rights. It is one of the most essential basic human rights in a democratic state. The right to life does not mean a mere physical existence or the right to live a lifeless life. The right to life includes the right to live with human dignity and all that goes along with it, namely, the basic necessities of life such as adequate nutrition, clothing and shelter over the head and facilities for reading, writing an expressing oneself in diverse forms, freely moving about and mixing and commingling with fellow human beings